Design strategies for lab-on-a-molecule probes and orthogonal sensing. (30th October 2014) - Chen, Kun; Shu, Qinghai; Schmittel, Michael
Abstract : Multianalyte chemosensors are most successful when they operate on selective sensing and signaling modes that are based on different detection channels, orthogonal binding, orthogonal reaction mechanisms and/or differing kinetic features. Abstract : This review highlights the currently exploited working concepts of lab-on-a-molecule probes, with a particular focus on what is required for multianalyte detection and quantification in competitive assays. Both, chemosensor and chemodosimeter approaches are considered. The multifaceted design strategies and the orthogonal protocols are evaluated in order to identify and categorise the successful conceptions and to single out unknown territory and challenges for future work.